Preparation for Viva voice - Gaanty Pragas, Maniam (Penerbit UMP, 2017)
This module delivers a stepwise preparation for the oral examination, the viva voce, of research candidates. It presents the needs for such examination and guiding the users towards achieving it successfully. It is essential to understand the very needs for viva voce at earlier stage possible, in order to cater for the research activities towards satisfying its needs. There are many misconceptions about the viva voce, for instance, the belief that it is a ‘defence’ which erroneously positions the students in a defensive manner throughout the oral session